2023
DOI: 10.1093/femsml/uqad009
|View full text |Cite
|
Sign up to set email alerts
|

Role of (p)ppGpp in antibiotic resistance, tolerance, persistence and survival in Firmicutes

Abstract: The stringent response and its signaling nucleotides pppGpp and ppGpp have been subject of intense research since the discovery of (p)ppGpp in 1969. Recent studies have revealed that the downstream events that follow (p)ppGpp accumulation vary among species. Consequently, the stringent response as initially characterized in Escherichia coli largely differs from the response in Firmicutes (Bacillota), wherein synthesis and degradation of the messengers (p)ppGpp is orchestrated by the bifunctional Rel enzyme wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…In addition, cdA likely inhibits the RCK_C domain containing protein EriC, a chloride channel protein necessary to reestablish the ionic balance after osmolyte uptake 27 . Lastly, binding of cdA to the small CBS domain protein CbpB abolishes the CbpB-Rel allosteric interaction leading to decreased (p)ppGpp synthase activity 38 , which is a conserved mechanism of antibiotic tolerance 58,59 .…”
Section: Joint Regulation Of Osmolyte Transporter Activity and Expres...mentioning
confidence: 99%
“…In addition, cdA likely inhibits the RCK_C domain containing protein EriC, a chloride channel protein necessary to reestablish the ionic balance after osmolyte uptake 27 . Lastly, binding of cdA to the small CBS domain protein CbpB abolishes the CbpB-Rel allosteric interaction leading to decreased (p)ppGpp synthase activity 38 , which is a conserved mechanism of antibiotic tolerance 58,59 .…”
Section: Joint Regulation Of Osmolyte Transporter Activity and Expres...mentioning
confidence: 99%
“…It describes the ability of bacteria to survive by slowing down metabolic cascades, and it is often referred to as phenotypic resistance. , Antibiotic tolerance and persistence may lead to the emergence of antibiotic resistance as persistence provides a viable group of cells with time in which the resistant mutants can emerge by de novo chromosomal mutations or horizontal gene transfer. , A recent de novo study demonstrated that M. tuberculosis cells exposed to lethal concentrations of antibiotics would generate antibiotic tolerance, and such cells could become resistant to the same antibiotics . Most antibiotics target active metabolic processes including replication and translation, and decreased growth rate may leads to multidrug tolerance . The stringent response has also been implicated in the downregulation of the genes required for growth in bacteria, including ribosome and cell wall synthesis. , The inhibition of growth by stringent response indirectly protects the cells from stress and antibiotics that usually target pathways involved in growth and metabolism.…”
Section: Role Of Rel and Relz In Antibiotic Tolerancementioning
confidence: 99%
“… 82 Most antibiotics target active metabolic processes including replication and translation, and decreased growth rate may leads to multidrug tolerance. 83 The stringent response has also been implicated in the downregulation of the genes required for growth in bacteria, including ribosome and cell wall synthesis. 84 , 85 The inhibition of growth by stringent response indirectly protects the cells from stress and antibiotics that usually target pathways involved in growth and metabolism.…”
Section: Role Of Rel and Relz In Antibiotic Tolerancementioning
confidence: 99%
“…The stringent response in persister cells is initiated through activation of the alarmone guanosine-5′-(tri)diphosphate-3′-diphosphate ((p)ppGpp), altering cellular physiology through transcriptional changes in populations with low metabolic activity, which consequently relocate cellular resources and ensure the survival of the bacterium [ 84 ]. Most antibiotics target active metabolic processes, and with this immediate shut-down of metabolism and growth, high levels of (p)ppGpp make bacteria insensitive to the actions of antibiotics [ 85 ]. A stringent response makes Pseudomonas aeruginosa biofilms tolerant to fluoroquinolones, meropenem, and gentamycin by preventing the accumulation of reactive oxidative species (ROS), which is considered a common mechanism by which antibiotics kill bacteria [ 86 , 87 ].…”
Section: Mechanism Through Which Biofilms Combat Antibioticsmentioning
confidence: 99%